BIMBINGAN DAN PELATIHAN PEMBUATAN LAPORAN KEUANGAN MELALUI APLIKASI MS OFFICE EXCEL DI KOPERASI UNIT DESA - Suryadi Suryadi; Edi Winarto; R. Setiawan; Ludfi Djajanto; Andi Asdani (Publisher UPT P2M Politeknik Negeri Malang, 2022)
Cooperatives are business organizations that are run for the common good with the aim of prospering its members. The Dau Village Unit Cooperative (KUD) in the common interest needs improvements. Among them are improvements in increasing cooperation or mutual cooperation, improving financial and asset administration as well as improvements in the presentation of financial statements and SHU. On the other hand, serving the purchase and improvement of store management belonging to KUD Dau also needs monitoring and business improvement. The awards that have been obtained at that time need to be achieved again so that the welfare of the members becomes better. Village Unit Cooperatives need support from various parties to exist again, especially the management of cooperatives professionally, starting from financing, administration, management of goods and services as well as financial reports, as well as improvements in SHU reporting. This issue must be immediately addressed by the parties concerned. information regarding the current condition of the KUD, administrative and financial management has been restructured so that there will be no more chaos in the preparation of financial statements and administering assets.The collaboration between the Polytechnic and the KUD management is one of the supports from the academic community to improve skills related to financial administration, especially the Balance Sheet and financial reports in general through Ms Office Simple Excel training.